Factors that contribute towards graduate employability in the two previously disadvantaged Eastern Cape tertiary institutions - Jali, Enkosi (Rhodes University, 2026)
The study investigated the factors that contribute to the job acquisition by graduates from two historically disadvantaged universities in the Eastern Cape region of South Africa. A quantitative research approach was adopted, using secondary data analysis from the 2015 National Student Financial Aid Scheme (NSFAS) graduates from the University of Fort Hare (UFH) and Walter Sisulu University (WSU). The study's first objective was to determine the relationship between direct signals (University Affiliation, CESM Category, and NQF Level) and the dependent variable (immediate job acquisition after one year registered with South African Revenue Services). Data analysis was conducted using descriptive statistics analysis. The findings of the study reveal significant associations between certain independent variables and the direct and probabilistic signals. Specifically, the findings from University Affiliation showed that the University attended has no effect on employment outcomes, nor does the CESM Category (the graduate’s field of study) matter when searching for jobs after graduation. The study showed a positive effect between NQF Level and employment outcomes with NQF Level 6 graduates having the highest employment rate. The study’s second objective was to determine the relationship between probabilistic signals (gender and age) and employment outcomes. The gender ‘signal’ has a positive effect in terms of finding employment after graduation for both males and females. The group of 21 years or younger showed the highest employment rate when it comes to age, indicating a positive relationship between age and employment outcomes. Although the study was limited to only two universities, it has contributed to a clearer understanding of the complex roles that probabilistic and direct signals play in influencing employment outcomes in the Eastern Cape region.
Keywords: Employability (http://id.loc.gov/authorities/subjects/sh2005004875); Historically Black colleges and universities (http://id.loc.gov/authorities/subjects/sh2022006092); National Student Financial Aid Scheme (South Africa) (http://id.loc.gov/authorities/names/no2002082807); University of Fort Hare (http://id.loc.gov/authorities/names/n50066582); Walter Sisulu University for Technology & Science (http://id.loc.gov/authorities/names/no2005107025)